An Adaptive Chlamydia trachomatis-Specific IFN-γ-Producing CD4+ T Cell Response Is Associated With Protection Against Chlamydia Reinfection in Women - Bakshi, Rakesh K.; Gupta, Kanupriya; Jordan, Stephen J.; Chi, Xiaofei; Lensing, Shelly Y.; Press, Christen G.; Geisler, William M. (Frontiers in Immunology, 2018)
Background: Adaptive immune responses that mediate protection against Chlamydia trachomatis (CT) remain poorly defined in humans. Animal chlamydia models have demonstrated that CD4+ Th1 cytokine responses mediate protective immunity against reinfection. To better understand protective immunity to CT in humans, we investigated whether select CT-specific CD4+ Th1 and CD8+ T cell cytokine responses were associated with protection against CT reinfection in women. Methods: Peripheral blood mononuclear cells were collected from 135 CT-infected women at treatment and follow-up visits and stimulated with CT antigens. CD4+ and CD8+ T-cells expressing IFN-g, TNF-a, and/or IL-2 were assessed using intracellular cytokine staining and cytokine responses were compared between visits and between women with versus without CT reinfection at follow-up. Results: A CD4+TNF-a response was detected in the majority (77%) of study participants at the treatment visit, but a lower proportion had this response at follow-up (62%). CD4+ IFN-g and CD4+ IL-2 responses occurred less frequently at the treatment visit (32% and 18%, respectively), but increased at follow-up (51% and 41%, respectively). CD8+ IFN-g and CD8+ TNF-a responses were detected more often at follow-up (59% for both responses) compared to the treatment visit (30% for both responses). At follow-up, a CD4+IFN-g response was detected more often in women without versus with reinfection (60% versus 33%, P=0.005). Conclusion: Our findings suggest that a CT-specific CD4+ IFN-g response is associated with protective immunity against CT reinfection and is thus an important component of adaptive immunity to CT in women.